Cognitive Load and Learning Motivation in Junior High School Students: Beban Kognitif dan Motivasi Belajar pada Siswa Sekolah Menengah Pertama - Wahyuningtyas, Sinta Wahyuningtyas; Widyastuti, Widyastuti (Universitas Muhammadiyah Sidoarjo, 2025)
Background: Learning motivation is crucial for student achievement, particularly in junior high school where students face cognitive and emotional transitions. Specific Background: Cognitive load theory explains how excessive mental demands can hinder motivation and learning outcomes. Knowledge Gap: Few studies have quantitatively examined the relationship between cognitive load and learning motivation in the context of Indonesian junior high schools. Aim: This study investigates the relationship between cognitive load and learning motivation among 221 students at SMP Muhammadiyah 1 Sidoarjo. Results: Pearson correlation analysis shows a significant negative correlation (r = -0.404, p < 0.05), with cognitive load contributing 16.3% to learning motivation variance. Novelty: The study highlights the importance of considering students’ cognitive capacity when designing learning activities. Implications: Teachers are encouraged to adjust instructional methods to prevent cognitive overload and sustain students’ motivation. Highlights Negative correlation between cognitive load and student motivation Contribution of 16.3% in explaining motivation levels Supports instructional strategies to reduce mental burden Keywords: Cognitive Load, Learning Motivation, Junior High School, Quantitative Study, Correlation